Leadership of Change: Examination of transactional, transformational and charismatic leadership, and evaluation of the concept of charismatic leadership in the current information-driven business environment - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
Effective / efficient leadership has always been one of the most important ingredients every organization looks for. Preferably, a leadership of change that would enable the organization to carry out its operations effectively and engender good results to meet the organization’s goals. Every organization looks forward to employ the right leadership to goad the organization splendidly, and furthermore, attain competitive advantage. Competition amongst organizations to meet consumers’ needs is very keen, and it behooves on management to exhibit the best leadership style to achieve targets. Transformation and charismatic leadership styles have the upper hand in leadership of change to suit the current technological business environment. In view of this, directors of organizations are always putting in every effort and stretching every sinew to go above its limit to make sure the organization is sustained and satisfy shareholders’ interest. As one of their responsibilities, they need to appoint management with the requisite talents and skills to achieve expected results, and accomplish organizational goals.